Cumulative effective dose and cancer risk for pediatric population in repetitive full spine follow-up imaging: How micro dose is the EOS microdose protocol?. Issue 101 (April 2018) - Law, Martin; Ma, Wang-Kei; Lau, Damian; Cheung, Kenneth; Ip, Janice; Yip, Lawrance; Lam, Wendy
Abstract: Objective: To evaluate and to obtain analytic formulation for the calculation of the effective dose and associated cancer risk using the EOS microdose protocol for scoliotic pediatric patients undergoing full spine imaging at different age of exposure; to demonstrate the microdose protocol capable of delivering lesser radiation dose and hence of further reducing cancer risk induction when compared with the EOS low dose protocol; to obtain cumulative effective dose and cancer risk for both genders scoliotic pediatrics of US and Hong Kong population using the microdose protocol. Methods: Organ absorbed doses of full spine exposed scoliotic pediatric patients have been simulated with the use of EOS microdose protocol imaging parameters input to the Monte Carlo software PCXMC. Gender and age specific effective dose has been calculated with the simulated organ absorbed dose using the ICRP-103 approach. The associated radiation induced cancer risk, expressed as lifetime attributable risk ( LAR ), has been estimated according to the method introduced in the Biological Effects of Ionizing Radiation VII report. Values of LAR have been estimated for scoliotic patients exposed repetitively during their follow up period at different age for US and Hong Kong population. Results: The effective doses of full spine imaging with simultaneous posteroanterior and lateral projection for patients exposed at the age between 5 and 18 years using the EOS microdose protocol have been calculated within the range of 2.54–14.75 μSv. The corresponding LAR for US and Hong Kong population was ranged between 0.04 × 10 −6 and 0.84 × 10 −6 . Cumulative effective dose and cancer risk during follow-up period can be estimated using the results and are of information to patients and their parents. Conclusion: With the use of computer simulation and analytic formulation, we obtained the cumulative effective dose and cancer risk at any age of exposure for pediatric patients of US and Hong Kong population undergoing repetitive microdose protocol full spine imaging. Girls would be at a statistically significant higher cumulative cancer risk than boys undergoing the same microdose full spine imaging protocol and the same follow-up schedule.